PENGARUH PRINSIP KONFUSIANISME DALAM ARTIKULASI POLITIK LUAR NEGERI TIONGKOK UNTUK MENGHADAPI PENGARUH BARAT (Studi Kasus Counter –Discourse Tiongkok terhadap Gagasan Universalitas HAM Barat) - Indah Gitaningrum (HI 16 UMY 119, 2016)
*199 This paper aims to describe the influence of Confucianism in Tiongkok’s foreign policy concerned in the human rights issue as the counter of Western universality discourse. Since The Universal Declaration of Human Rights was ratified in 1948, all nations have committed to agree in uniformity and implement it into an action in the name of human rights based on the universality. The human rights issue influence the relation among states and effecting in world political sphere.The result shows that culture,ideology and beliefs system have an important role in determining states’ foreign policies